Electron and spin injection in short-channel organic semiconducting devices - Alborghetti, Simone (Trinity College (Dublin, Ireland). School of Physics, 2012)
The realization of an active device that combines electric control of the source-drain current, as in transistors, with the memory effect of spin valves, has long been sought for the next generation spin electronics. The development of the field depends upon the existence of materials and structures that may be used as effective spin-polarized current injectors, transmitters, manipulators and detectors. Spin injection into semiconductors at a contact with a ferromagnetic metal is one of the possibilities that are currently being explored. The experiments described in this thesis are devised to explore the problem of spin injection into organic semiconductor at the metal /organic interface. In the first chapter, the theory of Schottky junctions and tunneling contact is presented; experimental results on various approaches towards the detection of spin-polarization using Schottky barriers are then presented, followed by the illustration of the models to describe charge transport mechanisms in organic mediums.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin